(untitled) (Research, Society and Development, 2022)
The Coronavirus pandemic, caused by the SARS-CoV-2 virus, has brought to light great discussions regarding the current Brazilian and global system of integrated health systems, as well as the discussion of preventive methods of various pathologies, from local levels to the global, among the most discussed preventive methods, is vaccination as an efficient preventive and pandemic control method. Within this context, the objective was to evaluate the profile of family members of medical students in relation to the need and importance of vaccination against COVID-19. The methodology was established in the form of an investigative cross-sectional study, having as a population universe family members of medical students from a private teaching institution in the city of Porto Velho-RO. Given the ethical precepts of research and human experimentation, having as inclusion and exclusion criteria, acceptance of the Free and Informed Consent Term. Of the respondents, 54.4% (49/90) were female and 45.6% (41/90) were male, 55.6% (50/90) are single, 35.6% (32/90) are married. and divorced 5.6% (5/90). The self-reported color presented was 47.8% (43/90) for brown, 41.1% (37/90) for white, 3.3% (3/90) for yellow, 4.4% (4/90) for black and 3.3% (3/90) were unable to declare. In terms of religious belief, 54.4% (49/90) were evangelical, 37.8% (34/90) were Catholic, 3.3% (3/90) were atheist, 2.2% (2/90) 90) spiritists and other religions 2.2% (2/90). In a study carried out by Paula et al., (2016), it was shown that 83.0% of the medical students interviewed did not have full adherence to vaccination protocols against influenza in a pandemic and post-pandemic period of the same pathology, in the years from 2010 to 2011. In conclusion, when evaluating the perception of family members of medical students, in relation to the need and importance of vaccination against COVID-19, different positions were observed in relation to efficacy and safety.